A client-server implementation of the MSU-IIT Registration System using Linux POSTGRESQL - Dimamay, Wilfredo A. (The Mindanao Forum: official journal of the MSU-Iligan Institute of Technology, 2003)
The Internet has paved the way for the widespread development and distribution of open-source software tools. However, their free availability has led many organizations to think that these tools are not suitable for use in mission-critical applications because of reliability and security issues. This project is an attempt to test the reliability and sustainability of the Linux and PostgreSQL open software tools as the major components of a mission-critical institutional application such as the MSU-IIT registration system. Implementation results showed the high reliability and sustainability of such tools, thus drastically reducing the cost of applications software development and implementation for any institution that would utilize them.